Journal of Ophthalmic Inflammation and Infection - Pavesio, Carlos
The Journal of Ophthalmic Inflammation and Infection is a peer-reviewed open access journal published under the brand SpringerOpen. It presents current clinical and experimental research on a range of ophthalmic inflammation and infection topics. Coverage includes original studies, review articles, brief reports, case reports, photo essays, and expert commentary on challenging cases. The journal reflects geographical variations in incidence of diseases as well as different treatment modalities worldwide. This is the official journal of the International Ocular Inflammation Society (IOIS), and the editorial board includes international experts in the field of ophthalmic inflammation and infection.